Governance and ownership in Malaysia: their impacts on corporate performance - Nazli Anum Mohd Ghazali (Emerald Publishing Limited, 2020)
The aim of this paper is to examine the relative influence of regulatory enhancements relating to corporate governance and attributes of business traits on performance of Malaysian listed companies.Regression analysis was performed on all 742 non-financial main board companies listed on Bursa Malaysia using data from 2013 annual reports.The results show that the number of board meetings held during the year, role separation and board size have a significant impact on corporate performance. By contrast, independent directors, government ownership and director ownership do not influence corporate performance.The study investigated non-financial companies for the financial year 2013. Hence, the results may not apply to financial companies and other years. Future research can perhaps include all types of listed companies and carry out a longitudinal study to gain more comprehensive results and understanding on the relationship between corporate governance and corporate performance. Additionally, future research could also consider employing a different methodology to further unveil factors influencing corporate performance.The above findings provide new evidence of the effectiveness of the Malaysian Code on Corporate Governance in improving company performance. The significance of board meetings, role separation and board size shows the importance of internal governance in shaping company processes and hence performance.The result suggests that although the Malaysian Code on Corporate Governance follows the corporate governance code of developed countries, the applicability of the recommendations to a developing country is evidenced. Companies in Malaysia are predominantly government-owned or closely held, but it appears that role separation matters even in these types of companies in achieving better performance.